2020
DOI: 10.1161/jaha.119.015355
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Lipoprotein (a) With the Requirement for a Peripheral Artery Operation and the Incidence of Major Adverse Cardiovascular Events in People With Peripheral Artery Disease

Abstract: Background The aim of this study was to assess the relationship between serum lipoprotein (a) (Lp[a]) concentration and the requirement for peripheral artery disease ( PAD ) operations or incidence of major adverse cardiovascular events. Methods and Results A total of 1472 people with PAD presenting with intermittent claudication (n=355), abdominal aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 49 publications
1
44
0
4
Order By: Relevance
“…Although not in the scope of this review article, in addition to coronary artery disease [ 40 ], a raised incidence of aortic valve stenosis and coronary artery calcification has also been described in association with elevated Lp(a) [ 41 , 42 , 43 , 44 ]. As reviewed elsewhere [ 45 , 46 ], Lp(a) can exacerbate pathophysiological processes in calcific aortic disease, a progressive disorder that impairs the valve motion and restricts the ventricular outflow.…”
Section: Introduction—an Overviewmentioning
confidence: 99%
“…Although not in the scope of this review article, in addition to coronary artery disease [ 40 ], a raised incidence of aortic valve stenosis and coronary artery calcification has also been described in association with elevated Lp(a) [ 41 , 42 , 43 , 44 ]. As reviewed elsewhere [ 45 , 46 ], Lp(a) can exacerbate pathophysiological processes in calcific aortic disease, a progressive disorder that impairs the valve motion and restricts the ventricular outflow.…”
Section: Introduction—an Overviewmentioning
confidence: 99%
“…Lp(a) measurement using this method has been significantly correlated with a liquid chromatography-mass spectrometry method. 27 Interassay coefficient of variation of all measurements were <6%. 3 | RESULTS…”
Section: Clinical Review Of Pcsk9mab Therapymentioning
confidence: 85%
“…The Quantia Lp(a) assay used in our study is not fully isoform independent, but we have found a good agreement with a liquid chromatography-mass spectrometry method. 27 Duration of the follow-up period of 11 months may not be sufficient to fully assess the long-term safety profile of PCSK9mAb treatment. We did not specifically assess the effect of PCSK9mAb treatment on neurocognitive effects.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…The independent predictors of events were an increased Lp(a) level (RR 2.8, 95% CI 1.4–5.5, p = 0.003) and programmed hemodialysis (RR 2.23, 95% CI 1.04–4.78, p = 0.04) [ 15 ]. In an Australian study, involving 1472 patients with LEAD, it was shown that the level of Lp(a) ≥ 30 mg/dL was associated with the frequency of peripheral revascularization; however, no association was found between elevated Lp(a) level and the frequency of myocardial infarction, stroke, and death [ 16 ]. In our study, there was not any association found between Lp(a) and past myocardial infarction or ischemic stroke, which is most likely due to the fact that the studied cohort of patients with significant atherosclerosis of peripheral arteries has an initially increased level of Lp(a).…”
Section: Discussionmentioning
confidence: 99%